(untitled) (Tanzania Medical Journal, 2015)
Main objective: To determine the clinico-pathological presentation and management of odontogenic myxoma at Muhimbili National Hospital, Dar es Salaam Tanzania.Study design: A prospective descriptive study.Setting: The Oral Surgery and Oral Pathology Department and the Department of Histopathology and Morbid Anatomy, Muhimbili University of Health and Allied Sciences Methodology: Patients’ demographic features, clinical and radiological presentation and histological results were recorded in special forms. The treatment plan, the treatment procedure and the outcome of the treatment were also recorded. Follow ups were conducted at different intervals for a minimum of one year. OPG radiographs were used to assess whether there was presence of any signs of recurrence. Patients were asked on the presence of any complications or any disabilities resulting from the surgical treatment that affected their quality of life.Results: Twenty five cases of OM were seen during the five-year period. The age range was 3 to 56 years with a mean of 28.2 years. Majority (84%) of the cases were aged between 10 and 39 years. There was only one patient who was below 10 years of age. There were more females with OM than males with a male to female ratio of 1:1.5. Most (48%) of the lesions were located on the mandible with only 36% on the maxilla and the rest (16%) were soft tissue (peripheral) lesions. Radiographically the majority of the lesions appeared multilocular with a soap bubble appearance. Very few (four) showed a honeycomb appearance. None of the lesions was seen to have clear boundaries. Tooth displacement was apparent in 10 cases and root resorption was seen in 8 mandibular lesions. The hospital stay after treatment was moderately long. Postoperative complications included disfigurement in cases with big tumours, recurrence, loss of masticatory function and difficulties with speech in cases of maxillary OM.Conclusion: Aggressive local resections in both the maxilla and the mandible result in low rates of recurrence. Early suspicion of the possibility of existent of OM, early reporting by patients and appropriate referrals could be the only possible means of minimizing such complications and improving the postoperative quality of life.